2012
DOI: 10.1534/genetics.111.137844
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Polarity Depends on Phosphatidylinositol Signaling Regulated bymyo-Inositol Monophosphatase inCaenorhabditis elegans

Abstract: Although neurons are highly polarized, how neuronal polarity is generated remains poorly understood. An evolutionarily conserved inositol-producing enzyme myo-inositol monophosphatase (IMPase) is essential for polarized localization of synaptic molecules in Caenorhabditis elegans and can be inhibited by lithium, a drug for bipolar disorder. The synaptic defect of IMPase mutants causes defects in sensory behaviors including thermotaxis. Here we show that the abnormalities of IMPase mutants can be suppressed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Both behavioral and localization defects in ttx-7 mutants were rescued by either expression of ttx-7 in adults, forced expression of human IMPase proteins, or by inositol supplementation. [23][24][25] As shown by Tanizawa et al, 23 the synaptic localization defects in ttx-7 mutants occurred exclusively in RIA neurons. In addition, this study showed that inositol monophosphatase is involved in a specialized part of cell phosphatidylinositol metabolism.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Both behavioral and localization defects in ttx-7 mutants were rescued by either expression of ttx-7 in adults, forced expression of human IMPase proteins, or by inositol supplementation. [23][24][25] As shown by Tanizawa et al, 23 the synaptic localization defects in ttx-7 mutants occurred exclusively in RIA neurons. In addition, this study showed that inositol monophosphatase is involved in a specialized part of cell phosphatidylinositol metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…8 IMPA1 has an essential role in maintaining neuronal polarity in the mature nervous system as demonstrated by studies on the Caenorhabditis elegans gene, ttx-7, its only gene to encode an inositol monophosphatase. 23,24 Mutations in ttx-7 cause defects in sensory behavior and localization of both pre-and post-synaptic proteins in RIA neurons and pivotal interneurons. Both behavioral and localization defects in ttx-7 mutants were rescued by either expression of ttx-7 in adults, forced expression of human IMPase proteins, or by inositol supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, IMPase plays an essential role in maintaining neuronal polarity as demonstrated by studies on the Caenorhabditis elegans gene, ttx-7, which is the only nematode gene to encode an IMPase. Mutants of ttx-7 are defective in thermotaxis due to disruption of membrane polarity in the RIA neuron (54,55) and can be rescued by enforced expression of human IMPA1 or IMPA2 (21), suggesting that mammalian IMPases and nematode Ttx-7 play similar roles in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A lithium induced inhibition of kinesin light chain phosphorylation by GSK-3 (Morfini, Szebenyi et al 2002) impacts axonal transport and could ultimately result in modification of synaptic vesicle populations upon chronic treatment. Another possible presynaptic mechanism could be via the reduction of brain inositol levels (Allison and Stewart 1971) and interfering with the PIP 2 /IP 3 -signaling (Berridge, Downes et al 1989;King, Teo et al 2009;Kimata, Tanizawa et al 2012), which in turn affects both exo and endocytosis (Milosevic, Sorensen et al 2005;Antonescu, Aguet et al 2011;van den Bogaart, Meyenberg et al 2011;van den Bogaart, Meyenberg et al 2012). …”
Section: Introductionmentioning
confidence: 99%